NUTRITIONAL STATUS BASED ON PROVIDING ASI AND MP-ASI PATTERNS IN UNDER TWO YEARS OLD CHILDREN IN THE AREA OF PUBLIC HEALTH CENTER 1 DENPASAR SELATAN - Ni Putu Devi Ary Santhi (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2021)
Data from Public Health Center I Denpasar Selatan in Sesetan Village amounted to 45.55% who passed Exclusive Breastfeeding, for Sidakarya Village at 47.92% who passed Exclusive Breastfeeding, and Panjer Village 51.49% passed Exclusive Breastfeeding. The purpose of this study was to determine nutritional status, identify patterns of breastfeeding, identify the age of MP-ASI begins, identify the type of MP-ASI that was first given in the working area of Public Health Center I Denpasar Selatan.This study was an observational study with a cross sectional design. The type of data consists of primary data (sample and identity of respondents, pattern of breastfeeding, pattern of MP-ASI giving, anthropometric measurements) and secondary data (geographical location, number of workers, and health services). Data collection is done by interviewing with the help of identity forms and questionnaires and measuring weight and height. Processing data obtained will be analyzed descriptively.Based on the research conducted, the results obtained were, malnutrition status was 21.98%, normal nutritional status was 71.43% and excess nutritional status was 6.59%, breastfeeding pattern was exclusive breastfeeding 51.85%, initial MP-ASI administration, ie 49, 46% and the type of MP-ASI was given for the first time, namely the type of MP-ASI of 62.64%. The suggestion given by the researchers is that health workers must pay more attention to being able to increase exclusive breastfeeding by giving counseling to the people most affected by having a baby. To avoid the introduction of MP-ASI too early, it needs to be given an embassy with emphasis through counseling and providing the material itself with adequate breast feeding until the age of 6 months (without the provision of MP-ASI).Keyword : nutrition status, exclusive breast feeding, MP-ASI